Producing for TV and Video - Kellison, Cathrine (Focal Press, 2012)
Producing for TV and Video is a must-read for anyone interested in a career in TV production. This comprehensive book explains the role of the TV producer in detail, including in-depth descriptions of a producer's day-to-day duties and tasks and a big picture overview of the production process in general and how the producer fits in. Complete with interviews and insights from production professionals in all areas of television, such as reality television and children's programming, Producing for TV and Video will provide you with an understanding of the TV production process and the role of the TV producer from beginning to end. The accompanying CD contains forms that you will inevitably need during your production.